SELF-DIRECTED PROFESSIONAL DEVELOPMENT AND HEUTAGOGY: INSIGHTS FROM THE BRITISH COUNCIL MINI-EVENT - The, Hery Yanto (STKIP Persada Khatulistiwa Sintang, 2025)
This research delves into the fusion of heutagogy principles with self-directed learning (SDL) to elevate my growth as a second language teacher-educator. Through the lens of intuitive inquiry, I reflect on my evolution from an applicant to a presenter at the British Council Mini-Event, where I shared my teaching insights. This qualitative approach, distinct from traditional empirical methods, facilitates a profound personal assessment, capturing the transformative journey of independent learning and achieving goals. The study underscores how heutagogy—a framework centered on learner autonomy—works in tandem with SDL to nurture educator independence, resilience, and creativity. The insights gained shed light on navigating the hurdles of preparing for international conferences, mentorship, and effective presentation, providing a blueprint for teacher professional development. By chronicling this experience, I hope to motivate other educators to embrace self-directed learning strategies, illustrating that reflective and intuitive research can produce significant performance indicators and inspiring milestones. This study adds to the conversation on alternative pathways for professional development, championing heutagogy and SDL methodologies to empower educators in charge of their lifelong learning journey.